(untitled) (River Edge, NJ, 2002)
Proceedings of the conference on Semigroups, Algorithms, Automata and Languages, organized at the International Centre of Mathematics, May-July 2001 in Coimbra, Portugal. For researchers, academics and graduate students in pure mathematics and computer science.
Keywords: Semigroups,Algorithms,Machine theory,Formal languages; Lý thuyết máy,Thuật toán